2015
DOI: 10.1111/nyas.12708
|View full text |Cite
|
Sign up to set email alerts
|

The biology of Plasmodium vivax explored through genomics

Abstract: Malaria is a mosquito-borne disease caused by the Plasmodium parasite. Of the four Plasmodium species that routinely cause human malaria, P. vivax is the most widespread species outside Africa, causing ~ 18.9 million cases in 2012. P. vivax cannot be cultured continuously in vitro, which severely hampers research in non-endemic and endemic countries alike. Consequently, whole-genome sequencing has become an effective means to interrogate the biology of the P. vivax parasite. Our comparative genomic analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Brazilian P. vivax isolates (n = 13) were obtained from patients attending a tertiary healthcare centre in Manaus (Amazonas State) [ 19 ]; Colombian parasite samples (n = 35) were collected in four different malaria-endemic regions described elsewhere [ 20 ]; Honduran samples (n = 12) were collected at the University Hospital located in Tegucigalpa, and its origin was determined to seven different localities throughout the country. Additionally, a total of 222 sequences reported to the GenBank and PlasmoDB originally from South Korea [ 17 ], North Korea [ 18 ], India and Indonesia [ 18 ], Thailand and Vanuatu [ 21 ], Mexico, Peru, Thailand and Myanmar ( Plasmodium vivax Hybrid Selection initiative, Broad Institute [ 22 , 23 ], and reference sequences from Brazil, India, Mauritania, and North Korea were used for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Brazilian P. vivax isolates (n = 13) were obtained from patients attending a tertiary healthcare centre in Manaus (Amazonas State) [ 19 ]; Colombian parasite samples (n = 35) were collected in four different malaria-endemic regions described elsewhere [ 20 ]; Honduran samples (n = 12) were collected at the University Hospital located in Tegucigalpa, and its origin was determined to seven different localities throughout the country. Additionally, a total of 222 sequences reported to the GenBank and PlasmoDB originally from South Korea [ 17 ], North Korea [ 18 ], India and Indonesia [ 18 ], Thailand and Vanuatu [ 21 ], Mexico, Peru, Thailand and Myanmar ( Plasmodium vivax Hybrid Selection initiative, Broad Institute [ 22 , 23 ], and reference sequences from Brazil, India, Mauritania, and North Korea were used for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…vivax DNA from clinical samples from Brazil has been a major challenge for genome sequencing projects, because (a) blood-stage parasite densities are typically very low [ 15 ], (b) clinical blood samples are heavily contaminated with human DNA from leukocytes, and (c) methods for long-term in vitro propagation of P . vivax are neither practical nor widely reproducible [ 16 18 ]. Here, we combined an improved sample preparation strategy, for reducing human DNA contamination and increasing target parasite's DNA yield, with next-generation genome re-sequencing to examine a local population of P .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature [23-33], we identified 64 gene regions that are potentially related to erythrocyte binding in P. vivax (Supplementary Table 1). These included the DBP (duffy binding protein), EBP (erythrocyte binding protein), MSP (merozoite surface protein), and RBP (reticulocyte binding protein) multigene families, the tryptophan rich antigen gene family ( TRAg ), GPI-anchored microanemal antigen ( GAMA) , microneme associated antigen ( MA) , rhoptry associated adhesin ( RA) , high molecular weight rhoptry protein 3 ( RHOP 3), and rhoptry neck protein ( RON) genes.…”
Section: Methodsmentioning
confidence: 99%
“…Members of the erythrocyte binding gene family, including reticulocyte binding proteins ( RBP s), Duffy-binding proteins ( DBP s), and merozoite surface proteins ( MSP 3 and MSP 7) have been previously shown to exhibit high sequence variation in P. vivax [20, 30]. The polymorphisms in RBP 1 and RBP 2 genes may relate to an increased capability of erythrocyte invasion by P. vivax [31-33]. It has been suggested that Pv RBP 2b-TfR1 interaction is vital for the initial recognition and invasion of host reticulocytes [34], prior to the engagement of PvDBP1 and Duffy antigen chemokine receptor ( DARC ) and formation of a tight junction between parasite and erythrocyte [35].…”
Section: Introductionmentioning
confidence: 99%